TEXTURAL ANALYSIS AND HYDRAULIC CHARACTERISTICS OF AJALI SANDSTONES OF OBOLLO-AFOR AND ENVIRONS IN ANAMBRA BASIN, SOUTHEASTERN, NIGERIA - Onyeabor, Chinenye Florence; Ezike, Ejiofor Chinedu; Chukwunonyerem, Stephen Chinaecherem (FUDMA JOURNAL OF SCIENCES, 2025)
The movement and storage of groundwater are determined by the porosity and hydraulic conductivity of the medium, which defines its permeability. Hydraulic conductivity depends on both the properties of the porous material and the fluid, and it has long been linked to the grain-size distribution of granular media. This study highlights the textural characteristics and hydraulic conductivity of Ajali Sandstone in Obollo-Afor area (southeastern Nigeria). The investigation approach involved field sampling and collection of 12 sandstone samples from different outcrop locations followed by laboratory studies such as grain size analysis. Grain size analysis and textural studies show that the sandstones mean range from 0.96-1.87 (av. 1.52). Other parameters such as coefficient of uniformity (Cu) range from 2.133 to 4.263 (av. 0.399), while sorting values of 0.83-1.10 (av. 0.96) imply moderately sorted sediments. The sandstones are mostly platykurtic and coarse skewed indicating sand of fluvial origin ranging from channel floor, point bar to braided rivers. Analysis shows that the sediments were deposited in beach/shallow agitated and fluvial agitated environments. The Ajali Sandstone porosity values range from 36.53%-42.6% (av. 39.9) and the hydraulic conductivity values of 2.579-68.101m/day (av. 43.741m/day). These values of porosity and hydraulic conductivity are indications of high specific yield for the sandstone of the study area.